THE CLASS-CONTESTATION IN JANE AUSTEN’S EMMA - Eko Budi Setiawan (Humaniora Scientia, 2018)
This study discusses a novel entitled Emma written by Jane Austen. Emma portrays the lives of different classes in Victorian society through its characters. This classification of people is due to some factors such as economics, ideology, taste, hegemony and language. Each character in Emma is the representation of the classes exists in the novel.The problem related to the topic of this researchis the class-formation of Victorian Society depicted in Emma. In order to answer the problems, a Marxist theory by Jameson is employed. This theory is applicable in Emma, since the characters are engaged to each other not only based on the economic as a means of production, but also on the ideology, social and cultural aspects.Based on the analysis, the class formation in Emma is not only based on the economics of each character, but also based on the ideology, taste and hegemony, and language. They, altogether, form classes and influence the characters in maintaining their class status. People who possess huge economic base are the representation of the dominant class, whereas the others represent the laboring class. Because of their economic base, Emma Woodhouse and George Knightley could have comfortable lives. Therefore, they are the representation of the dominant class. On the contrary, Miss Bates and Robert Martin have hard lives and they are the representation of the laboring class. Each member of the class tries to climb their status, unexceptionally Emma Woodhouse and George Knightley. They act differently in order to maintain their class status.